The âKnowledge Gapâ and âDeficient Performance Gapâ between Auditors and Corporate Managers: An Empirical Study in Malaysia - Lee, Teck Heang; Md. Ali, Azham (Gadjah Mada International Journal of Business, 2008)
This paper reports the findings of a questionnaire survey of âknowledge gapâ and âdeficient performance gapâ conducted in Malaysia on auditors and corporate managers. A total of 47 auditors and 72 corporate managers in Klang Valley responded to the survey. The aims of the study are two folds. Firstly, it ascertains the knowledge of the auditors and corporate managers of the auditorsâ duties as required by the Malaysian Companies Act 1965 and the Malaysian Approved Standards on Auditing. Secondly, it elicits the perceived performance of auditors in relation to these required duties. The results of the study indicate the existence of âknowledge gapâ and âdeficient performance gapâ between auditors and corporate managers. Overall, the results indicate that: (1) the auditors in Malaysia are knowledgeable about their duties and (2) the corporate managers have limited knowledge of auditorsâ duties and they are less satisfied with some of the duties performed by the auditors.